Blood pressure dynamics, peripheral blood flow parameters, and thyroid status compensation in patients with primary hypothyroidism and arterial hypertension - D. V. Kileynikov; Yu. A. Orlov (Кардиоваскулярная терапия и профилактика)
Aim. To study the dynamics of blood pressure (BP) and peripheral blood flow parameters during thyroid status compensation in patients with primary hypothyroidism (PHT) and arterial hypertension (AH). Material and methods. The main group (MG) included 70 patients with decompensated PHT and AH (64 women, 6 men; mean age 54,0±1,2 years). The control group (CG) included 40 women with essential AH (mean age 53,4±2,3 years). All participants underwent 24-hour BP monitoring (BPM), high-frequency Doppler ultrasound, with maximal systolic (Vs) and end diastolic (Vd) velocity assessment, as well as reactive hyperemia test (RHT). Results. MG and CG patients were comparable by day and night-time levels systolic and diastolic BP (SBP, DBP). Hormone replacement therapy in MG patients resulted in a significant SBP reduction during the day (-5,6 %; p<0,01) and the night (-4,3 %; p<0,05). At baseline and after RHT, Vs was 21 % higher in PHT patients than in the CG (p<0,01). Thyroid status compensation was associated with a 24 % Vs reduction (p<0,05), and no statistically significant Vs difference, comparing to the CG. Conclusion. In PHT and AH patients, thyroid status compensation resulted in a significant SBP decrease during the day and night, as well as in reduced Vs.